2023
DOI: 10.1021/acsami.2c21226
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of High-Efficiency (>14%) HTL-Free Carbon-Based All-Inorganic Perovskite Solar Cells by Passivation with PABr Derivatives

Abstract: Due to the advantages of low cost and good thermal stability, all-inorganic CsPbI 2 Br carbon-based perovskite solar cells (C-PSCs) without a hole transport layer have been rapidly developed in recent years. While the carbon electrode is in direct contact with the CsPbI 2 Br film, higher requirements are placed on the defects and energy level arrangement of the CsPbI 2 Br layer, which leads to the relatively low photoelectric conversion efficiency (PCE) of C-PSCs. Herein, propylamine hydrobromide (PABr) and it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 66 publications
0
9
0
Order By: Relevance
“…Surprisingly, under the optimal Zn­(Ac) 2 concentration of 0.5 mg/mL (other concentrations and corresponding device performances are shown in Table S2 and Figure S8), a significantly enhanced PCE of 14.20% ( J sc : 14.49 mA/cm 2 ; V oc : 1.226 V; FF: 79.95%) was achieved for the target CsPbI 2 Br C-PSCs, mainly due to its dramatically increased V oc and FF values. To our present knowledge, this PCE is among the highest efficiencies of the reported CsPbI 2 Br C-PSCs, further demonstrating the effective defect regulation for the Zn­(Ac) 2 -modified buried interface. ,,,, Considering the hysteresis phenomenon existing in this kind of device (Figure S9), we evaluate the steady power output (SPO) of CsPbI 2 Br C-PSCs operated at their maximum power point, as depicted in Figure b, which reveals steady PCEs of 11.41% and 13.07% for the control and target C-PSCs, respectively. The external quantum efficiency (EQE) spectra of both devices are presented in Figure c, enabling us to determine the integrated J sc values for the control and target devices as 13.95 and 14.06 mA/cm 2 , respectively.…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…Surprisingly, under the optimal Zn­(Ac) 2 concentration of 0.5 mg/mL (other concentrations and corresponding device performances are shown in Table S2 and Figure S8), a significantly enhanced PCE of 14.20% ( J sc : 14.49 mA/cm 2 ; V oc : 1.226 V; FF: 79.95%) was achieved for the target CsPbI 2 Br C-PSCs, mainly due to its dramatically increased V oc and FF values. To our present knowledge, this PCE is among the highest efficiencies of the reported CsPbI 2 Br C-PSCs, further demonstrating the effective defect regulation for the Zn­(Ac) 2 -modified buried interface. ,,,, Considering the hysteresis phenomenon existing in this kind of device (Figure S9), we evaluate the steady power output (SPO) of CsPbI 2 Br C-PSCs operated at their maximum power point, as depicted in Figure b, which reveals steady PCEs of 11.41% and 13.07% for the control and target C-PSCs, respectively. The external quantum efficiency (EQE) spectra of both devices are presented in Figure c, enabling us to determine the integrated J sc values for the control and target devices as 13.95 and 14.06 mA/cm 2 , respectively.…”
Section: Resultsmentioning
confidence: 80%
“…To our present knowledge, this PCE is among the highest efficiencies of the reported CsPbI 2 Br C-PSCs, further demonstrating the effective defect regulation for the Zn(Ac) 2 -modified buried interface. 33,35,41,52,53 Considering the hysteresis phenomenon existing in this kind of device (Figure S9), we evaluate the steady power output (SPO) of CsPbI 2 Br C-PSCs operated at their maximum power point, as depicted in Figure 5b, which reveals steady PCEs of 11.41% and 13.07% for the control and target C-PSCs, respectively. The external quantum efficiency (EQE) spectra of both devices are presented in Figure 5c, enabling us to determine the integrated J sc values for the control and target devices as 13.95 and 14.06 mA/cm 2 , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…[77] Therefore, the energy level alignment among the perovskite film and CTLs, as well as the interface properties of perovskite films (such as defect density, grain size homogeneity, and film roughness) play a critical role in determining the charge transport and trap-assisted charge recombination of the device, thereby influencing the performance of AIWPSCs. [56,74,[86][87][88] Consequently, much attention has been focused on this field. Yang and coworkers found that the top deposited polythiophene film can significantly suppress carrier recombination within the all-inorganic perovskite layer by passivating the interface defect states, which can effectively extend the carrier lifetime of the perovskite film (Figure 6a).…”
Section: Interface Modificationmentioning
confidence: 99%
“…One of such efforts is the significant improvement of stability in perovskite solar cells through the use of doping engineering to create a hole transport layer free of pinholes 35 . Investigations by other scientists have concentrated on creating effective PSCs employing novel kinds of hole-transport materials as replacement to Spiro-OMeTAD 36 , 37 , or PSCs without HTL that are suitable for streamlining the device’s ideal process, and further reduce manufacturing cost and as well prevents perovskite’s degradation 38 40 . There is no doubt that the absence of pinholes in HTM layer considerably increases the PSC’s device stability under operating environments 41 .…”
Section: Introductionmentioning
confidence: 99%